Język niderlandzki w Holandii i północnej Belgii: integracja czy dezintegracja? - Prędota, Stanisław (Studia Europaea Gnesnensia, 2010)
The article presents findings of Dutch and Belgian linguists concerning the rela-tions between the language of the Netherlands and its Flemish variety. First, the author provides characteristics of both ethnolects and of the social groups which use those. Subsequently, he analyses the existing lexical and pronunciation differences. In the final part, the author presents conclusions, different, as it turns out, for formal and colloquial language.